Aspectos endoscópicos no manejo da úlcera péptica gastroduodenal - Giordano-Nappi,José (2008)
Bleeding remains a common and a potential lethal complication for peptic ulcer disease. Multidisciplinary approach by endoscopists, surgeons and intensive care physicians is necessary to improve results for this severe complication. In this article we intend to introduce surgeons and intensive care physicians to endoscopic concepts and maneuvers commonly used in the treatment of bleeding peptic ulcer disease. Early clinical assessment and endoscopic evaluation are helpful to classify the severity of the bleeding episode. Two major achievements have changed the management of this complication: combined endoscopic therapy and proton pump inhibitors. The former consists of combining two different endoscopic methods to stop bleeding or prevent re-bleeding (e.g., injection of a sclerosing substance and thermal coagulation). Surgical treatment for peptic ulcer bleeding is indicated when endoscopic therapy fails or to prevent re-bleeding in high risk patients who presents with a spurting bleeding ulcer and shock. For the remaining situations, there are consistent evidences that a second endoscopic therapy should be attempted when re-bleeding occurs. Keywords: endoscopic hemostasis, recurrent bleeding, peptic ulcer bleeding, proton-pump inhibitor, non-variceal gastrointestinal bleeding.